The Cultural Philosophy Values in The “Denpasar-Style Bridal Makeup: Symbols and Meanings” Documentary Film - Ni Kadek Dwiyani; I Kadek Puriartha; Dewa Ayu Leliana Sari (Mudra Jurnal Seni Budaya, 2023)
Documentary film is a film genre that has a very important role in human civilization. Documentary films can "revive" everything that did not exist before, so that it can be known by a wide audience through visualization and verbal information that can be accounted for. One of the functions that documentaries also have is as a cultural educational medium that is easily accessed digitally by anyone, anywhere. This writing will examine the philosophical values that are visually transformed in the Cultural Documentary Film "The Balinese Bride Makeup: Symbols and Meanings". This writing uses a qualitative descriptive method, by providing explanatory descriptions of the results of the study using Documentary Film theory (Ayawaila: 2018) and Anthropological theory (Sare: 2007). The results obtained through this paper include findings on 3 cultural philosophical values contained in the documentary films used as research objects, as follows: 1) Character Education Values; 2) Values of Roles and Responsibilities, and 3) Cultural Inheritance Values.